Examining Validity and Reliability of a Mathematics Assessment Tool for K-2 Students (Journal of Education and Development, 2018)
The Primary Math Assessment (PMA) tool is increasingly being used in multiple districts in a northwestern state. The PMA provides both screening and diagnostic information in six domains to assess mathematical proficiency in young students in their early educational years. A previous study using multidimensional Rasch analyses found support for the PMA’s six-dimensional theoretical framework, and that the PMA is a reliable mathematics assessment for early grades. This study extended the examination of a Rasch model, implementing exploratory and confirmatory factor analysis, Item Response Theory, and Differential Item Functioning analyses. In doing so, this study found an IRT 2-PL model to fit best with these data and provided ways to improve the accuracy of measuring mathematical proficiency in early grades.